Defining and Classifying Corporate Social Costs: An Initiative to Enrich the Thought of Accounting for CSR - Younis A. Battal Saleh (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Purpose: This desk research aims to provide a clear and precise definition of the term